2003
DOI: 10.1016/s0926-860x(03)00154-6
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory behaviour during the partial oxidation of methane over cobalt wires and foils

Abstract: The oscillatory behaviour over cobalt wire and foil catalysts was examined at atmospheric pressure under various reaction temperatures and argon/methane/oxygen feed gas compositions for the partial oxidation of methane. Rough and porous oxide layers on the catalyst surface were confirmed by scanning electron microscopy (SEM) and X-ray diffraction (XRD) techniques. The results obtained from the experimental studies indicated that the oscillatory behaviour exhibited during methane oxidation was related to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Deng et al also reported that adding small amounts of ceria to the oxide support could help stabilise the oscillations. Other works by Zhang et al [17,18] concluded that oscillations may also be observed when using metallic nickel or cobalt foils. However, their intensities and frequencies were lower than what had been observed with palladium [16].…”
Section: Introductionmentioning
confidence: 95%
“…Deng et al also reported that adding small amounts of ceria to the oxide support could help stabilise the oscillations. Other works by Zhang et al [17,18] concluded that oscillations may also be observed when using metallic nickel or cobalt foils. However, their intensities and frequencies were lower than what had been observed with palladium [16].…”
Section: Introductionmentioning
confidence: 95%
“…Since cobalt is typically a good catalyst for methane partial oxidation [35,36], the acquirement of high OCV and power density was somewhat surprising. Fig.…”
Section: In Situ Reduction With Hydrogenmentioning
confidence: 99%
“…A wide class of these reactions is the oxidation of hydrocarbons over transition metals. For instance, self-sustained rate oscillations have been noted in the oxidation of methane, ethane, propane, and butane over supported and unsupported catalysts based on Ni, Co, Pd, Pt, Rh, and Ru [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The distinctive features of these oscillations are their long periods, ranging from several seconds to tens of minutes, and an induction period before the appearance of the regular oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the oscillations in the oxidation of propane over Ni exist when the propane/oxygen molar ratio ranges from 3/1 to 15/1 [25]. Besides, strong reaction-induced changes in the catalyst morphology are observed during the oscillations [11,15,23].…”
Section: Introductionmentioning
confidence: 99%